Screening of Proximal and Interacting Proteins in Rice Protoplasts by Proximity-Dependent Biotinylation - Lin, Qiupeng; Zhou, Zejiao; Luo, Wanbin; Fang, Maichun; Li, Meiru; Li, Hongqing (Frontiers in Plant Science, 2017)
Proximity-dependent biotin identification (BioID), which detects physiologically relevant proteins based on the proximity-dependent biotinylation process, has been successfully used in different organisms. In this report, we established the BioID system in rice protoplasts. Biotin ligase BirAG was obtained by removing a cryptic intron site in the BirA* gene when expressed in rice protoplasts. We found that protein biotinylation in rice protoplasts increased with increased expression levels of BirAG. The biotinylation effects can also be achieved by exogenous supplementation of high concentrations of biotin and long incubation time with protoplasts. By using this system, multiple proteins were identified that associated with and/or were proximate to OsFD2 in vivo. Our results suggest that BioID is a useful and generally applicable method to screen for both interacting and neighboring proteins in their native cellular environment in plant cell.